School leadership and Information Communication Technology. - Afshari, Mojgan; Abu Bakar, Kamariah; Wong, Su Luan; Abu Samah, Bahaman; Foo, Say Fooi (Sakarya University, Sakarya, 2008)
Leadership is an important component in guiding the teaching-learning process. Principal as school leaders have a major responsibility for initiating and implementing school change through the use of Information and Communication Technology (ICT) and can facilitate complex decision to integrate it into learning, teaching and school administration. Hence, educational leaders must understand, promote and implement the notion that technology integration is not about the technology; it is about focusing on the future generations and leading teachers to a change in pedagogy. However, few studies have empirically examined computer use by principals, their perceived computer competence and their leadership style. This paper will report on these issues from an initial analysis of a baseline data gathered from 30 secondary school principals in Tehran, a large province in Iran. Findings indicate that school principals are using computers for instructional and administrative purposes and they have moderate competency in computer applications. This paper also suggests that the idea of transformational leaders can enhance the computer use in schools. Hence, policy makers must design professional development programs, such as leadership studies, in order to teach the components of transformational leadership; idealized influence, inspirational motivation, intellectual stimulation and individual consideration to future administrators.